A cultura escrita nos anos iniciais do ensino fundamental: implicações pedagógicas da Teoria Histórico- Cultural - Lugle, Andreia Maria Cavaminami [UNESP] (2015)
The object of study of this doctoral thesis is the relations established between written culture and the appropriation of such language during the early years of Elementary School. My general objective is to understand the role written culture plays in the appropriation of written language during the early years of Elementary School, and reflect over its pedagogical implications, according to cultural-historical and Bakhtin's theories. I enumerate as specific objectives: a) to identify practices aiming the development of reading and writing in classes ranging from first to fifth grade of elementary school; b) to verify the concept elementary school students attribute to reading and writing; c) to understand how cultural-historical and Bakhtin's theories contribute to the comprehension of the written language appropriation process.The investigation was performed in a County Public School in the city of Londrina, Paraná, between the months of August/2013 and November/2014. The data collection instruments were classroom observations, interviews with 81 students from first to fifth grade of elementary school, and pedagogical actions developed with such students. Results revealed that the teaching promoted by schools concerning the appropriation of reading and writing is still guided by the acts of decoding and encoding, of mastering the relationship between sound and letter. The presence of written culture is restricted to textbooks, or to teachers' expository information, which directly limits the appropriation of written language as a cultural instrument, as well as the comprehension of its social function by students. As of these findings, I searched for indications regarding how to organize adequate conditions to the appropriation of written language substantiated on cultural-historical and Bakhtin's theories, and performed some procedures with such classes thereafter. I found possible a pedagogical practice that inserts students...